Nyquist Filters with Alternative Balance between Time- and Frequency-Domain Parameters. (1st October 2010) - Bobula Bobula, Marek Marek; Prokeš Prokeš, Aleš Aleš; Daněk Daněk, Karel Karel
Abstract : Designing matched pulse shaping filters with their cascade satisfying the Nyquist condition for minimum intersymbol interference constitutes an important task for almost all digital data radio transceivers processing an incoming data signal on the sample-by-sample basis. Despite their practical importance, there are only few sets of Nyquist filter definitions and design techniques to devise digital filter coefficients available for a designer. In this paper we propose a set of Nyquist filters that balance the time- and frequency-domain parameters in favor of a filter stop-band attenuation and residual intersymbol interference compared with the already existing Nyquist filter sets. Using a number of filter examples, this paper shows that the proposed Nyquist filters can be a good option for applications that need to fulfill strict limits of adjacent and alternate channel power attenuation while providing a low level of residual intersymbol interference and group delay of the digital filter.